THE CONFERENCE «RUSSIAN TROOPS IN FRANCE AND THE BALKANS (1916-1918) IN THE HISTORICAL MEMORY OF RUSSIA AND EUROPE», MOSCOW, 16-18 OF MAY, 2019 - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2019)
The article deals with an international scientific conference, entitled “Russian army in France and the Balkans (1916-1918) in historical memory of Russian and Europe”, held in Moscow, on May 16-18, 2019. It conveys the forum’s status, the focus of its work, geography of the participants and subject of scientific reports.